Effects of peripheral substitutions on the singlet oxygen quantum yields of monophthalocyaninato ytterbium(iii) complexes. Issue 28 (26th February 2015) - Zhang, Quanquan; Cheng, Guoe; Ke, Hanzhong; Zhu, Xunjin; Zhu, Nianyong; Wong, Wai-Yeung; Wong, Wai-Kwok
Abstract : A new monophthalocyaninato ytterbium(iii ) complex5 has been prepared and characterized. The effects of substituents on the relative singlet oxygen quantum yields of monophthalocyaninato ytterbium(iii ) complexes have been investigated. Abstract : A new monophthalocyaninato ytterbium(iii ) complex5 with eight 3, 5-di- t -butylphenoxyl substituents at peripheral positions is synthesized. X-ray structural analysis of5 ·CHCl3 ·MeOH reveals that the Yb 3+ ion is seven-coordinate, surrounded by four nitrogen atoms from the phthalocyaninate dianion and three oxygen atoms from the anionic tripodal LOMe − ligand LOMe − = [(cyclopentadienyl)tris(dimethylphosphito) cobaltate(iii )]. The effects of substituents on the relative singlet oxygen ( 1 O2 ) quantum yields of monophthalocyaninato ytterbium(iii ) complexes are investigated through comparison. It is found that the monophthalocyaninato ytterbium(iii ) complex has higher 1 O2 quantum yield than its corresponding phthalocyaninate ligand. The introduction of a 3, 5-di- t -butylphenoxy substituent on the microcycle can enhance the yield of singlet oxygen. Due to the heavy-atoms of both iodine and lanthanide ions, the ytterbium(iii ) complex4 based on tert -butyl and iodine substituted phthalocyanine ligands has the highest 1 O2 quantum yield (0.82).